Theoretical essence of innovative marketing - Tkachova, N. P.; Matrosova, V. O.; Veryutina, V. Ju.; Pererva, P. G. (Луцький національний технічний університет, 2022)
It is proposed to understand the marketing of innovations as activities aimed at finding new directions and ways of using the company's potential, developing new products and technologies on this basis, and promoting them to the market in order to more effectively meet the needs of consumers. way than competitors, thereby making a profit and providing conditions for long-term survival and development in the market.
Теоретична сутність інноваційного маркетингу
Keywords: innovative marketing; theoretical essence; methodology; technology; market; components